Design of an automated assembly line at ink bottling company [electronic resource] - Noor Izwan Ismail, 1987- (2010)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Industri)) - Universiti Teknologi Malaysia, 2010